Peningkatan Ekonomi Kreatif Masayarakat Pesisir Selili Manggar Melalui Pengolahan Hasil Perikanan Dan Laut - Doddy Suanggana; Alfian Djafar; Faisal Manta; Devy Setiorini Sa'adiyah; Aditiya Ramadhan; Muhammad Noor El-Haj; Myhammad Ibnu Habbil Sunarno; Vidi Apriany; Desly Angeline Sa’pangan; Dewa Ichwan Suharisma; Sofia Annisa; Adnan Rusdan (CV. Multi Kreasi Media, 2023)
Selili Village area which is located at Jalan Selili RT. 43 No. 11, Kec. Manggar, Kel. Balikpapan Timur, Balikpapan City is a village area in general, the area is on the coast near the sea. There the average occupation of its citizens is fishermen and fish sellers. Traveling to the location is quite easy, there is road access that can be passed by motorbikes and cars. There are differences in where the residents live, some live on the sea coast and some live in the mainland area. From the problems obtained during the survey, there is a solution to help the Selili Manggar area community, especially residents of RT. 43 in increasing the income from the fish they catch, namely in the form of processing fish into preparations that are easy to eat and accepted in the market. This processed fish can be in the form of fish balls, tempura, fish nuggets. It is usually favored by the market because it tastes good, is easy to cook by frying or boiling, and many small children like it. The proposed program in helping the community of RT. 43, namely conducting socialization from planning product results, how to market, product management, how to package attractively, after that fostering the output of this socialization and a product resulting from this community service activity, namely processed fish products from the sea, training on how to process and market products made, and socialization to local residents.